Analysis toward purchase decision determinant factors - Santoso, Aprih; Sispradana, Audi Redha (Asian Management and Business Review, 2021)
The problem with this research is that there is a tendency to decrease demand for Hemart brand cooking oil in 2018-2019. This makes it a challenge for the Hemart cooking oil product distributor company to find out the factors that influence the decline in purchases. This study aims to analyze brand image, product quality, promotion and knowledge of sales promotion on the purchasing decisions of PT. Transfarma Semarang Branch. The population in this study were all consumers of PT. Transfarma Semarang Branch, which amounted to 566 consumers, while the sampling technique used was a non-probability sampling technique with purposive sampling and the analytical tool used in this study was multiple linear regression. The results showed that the variables of consumer confidence, consumer experience and sales promotion had a positive and significant effect on purchasing decisions of PT. Transfarma Semarang Branch and the results of the adjusted R square value in the regression model were obtained at 0.584, which means that 58.4 percent of the purchasing decision variables can be explained by the variables of consumer confidence, consumer experience and sales promotion while the remaining 41.6 percent is explained by other variables outside of this study.